Ontological how and why: action and objective of planned processes in the food domain - Dooley, Damion; Naravane, Tarini (Frontiers in Artificial Intelligence, 2023)
The computational modeling of food processing, aimed at various applications including industrial automation, robotics, food safety, preservation, energy conservation, and recipe nutrition estimation, has been going on for decades within food science research labs, industry, and regulatory agencies. The datasets from this prior work have the potential to advance the field of data-driven modeling if they can be harmonized, but this requires a standardized language as a starting point. Our primary aim is to explore two interdependent aspects of this language: pursuing the granularity of process modeling sub-parts and parameter details, and the substitution of compatible inputs and processes themselves. A delicate semantic distinction - between categorizing planned processes by the objectives they seek to fulfill, versus categorizing them by the actions or mechanisms they utilize - helps to organize and facilitate this endeavor. To bring an ontology lens to process modeling, we employ the Open Biological and Biomedical Ontology Foundry ontological framework to organize two main classes of what will be the FoodOn upper-level material processing hierarchy according to objective and mechanism respectively. We include examples of material processing by mechanism, ranging from abstract ones such as “application of energy” down to specific classes like “heating by microwave”. Similarly, material processing by objective - often a transformation to bring about materials with certain qualities or composition - can for example range from “material processing by heating threshold” to “steaming rice”.